2005
DOI: 10.1111/j.1600-0404.2004.00366.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutation and polymorphism analysis of TSC1 and TSC2 genes in Indian patients with tuberous sclerosis complex

Abstract: This is the first molecular genetic study of TSC in an Indian population. A total of 12 mutations were detected in 24 Indian TSC families in TSC genes. All except one mutation were detected in the TSC2 gene. No variation was found in the promoter regions of either gene. As observed in the western and Japanese populations, the mutations were scattered across the TSC2 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 27 publications
1
15
0
1
Order By: Relevance
“…The phenotypic manifestations in affected persons vary greatly. In patients meeting standardized (Roach & Sparagana, 2004) clinical criteria for TSC, a disease causing mutation in either TSC1 or TSC2 is found in 75–85% of cases (Dabora et al, 2001; Ali et al, 2005; Sancak et al, 2005; Au et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenotypic manifestations in affected persons vary greatly. In patients meeting standardized (Roach & Sparagana, 2004) clinical criteria for TSC, a disease causing mutation in either TSC1 or TSC2 is found in 75–85% of cases (Dabora et al, 2001; Ali et al, 2005; Sancak et al, 2005; Au et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Even though for most TSC1 and TSC2 mutations there have been no consistent genotype/phenotype correlations between specific mutation types and associated clinical manifestations (Janssen et al, 1990; Niida et al, 1999; Dabora et al, 2001; Humphrey et al, 2004; Ali et al, 2005; Au et al, 2007), many studies show that TSC2 patients have overall both a higher incidence and more severe features of TSC than patients with TSC1 mutations, including more significant neurological, renal and other organ involvement (Jones et al, 1999; Dabora et al, 2001; Langkau et al, 2002; Sancak et al, 2005; Au et al, 2007). However there are also several missense mutations in TSC2 which have been associated with distinctly mild clinical features, such that some family members bearing these TSC2 missense mutations do not fulfill standard diagnostic criteria (Khare et al, 2001; O’Connor et al, 2003; Mayer et al, 2004; Jansen et al,2006).…”
Section: Introductionmentioning
confidence: 99%
“…More than 200 unique TSC1 mutations and 700 unique TSC2 mutations have been reported. In this study, we screened 4 TSC cases for mutations in all coding regions and exon-intron boundaries of the TSC1 and TSC2 genes, and 3 causative mutations in the TSC2 gene were detected in these cases, with a mutation rate of 75%, similar to that obtained previously (Ali et al, 2005;Camposano et al, 2009). van Slegtenhorst et al (1997 reported that approximately 10 to 30% of all TSC cases are due to mutations in the TSC1 gene, but no mutation was found in the TSC1 gene in our study.…”
Section: Discussionmentioning
confidence: 53%
“…In a few studies, where TSC1 and TSC2 promoter region analysis has been performed, the levels of mutations detected were either very low or null 17,18 .…”
Section: Resultsmentioning
confidence: 99%